P16.03 Cerebral gliom alters the peripheral CD4+ T helper cell phenotype. (9th September 2021) - Mohme, M; Maire, C; Rünger, A; Glau, L; Tolosa, E; Westphal, M; Lamszus, K
Abstract: BACKGROUND: Cancer is a systemic disease. Due to the exceedingly rare occurrence of metastasis of cerebral glioma, systemic alterations have, however, not been considered to play a major role in disease progression of glioma. CD4 + T helper (TH ) cells orchestrate the adaptive immune response in an antigen-specific, cytokine mediated manner. The aim of our study was to investigate how far cerebral glioma impacts the systemic CD4+ immune repertoire. MATERIAL AND METHODS: We performed flow-cytometry analysis of the peripheral blood CD4+ TH cell phenotype and cytokine production in 100 patients with IDHwt, 30 IDHmut and 16 IDHmut 1p19q co-deleted gliomas in comparison with age-matched healthy donors (HD). Data was analyzed using a Fortessa LSR and Diva software. Multiparameter analyses were performed using UMAP and SpadeVizR trees. The study was approved by the ethics committee (PV4904). RESULTS: We found a significant skewing of the peripheral immunophenotype in IDHwt glioma patients, showing a TH 1 expansion and reduced numbers of T follicular helper cells (TFH ), TH 1* and mucosa associated invariant T (MAIT) cells (p<0.001), while TH 2 and TH 17 percentages remained stable compared to IDHmut and HD. Although TH 1 cells were dominant in IDHwt patients (p<0.01), intracellular cytokine staining showed a reduction of IFNγ and TNFα production after in vitro stimulation, while IL-4 was significantly increased compared to HD (p<0.05). No alterations between all groups were observed in IL-2, IL-10 or IL-17 production. Profiling of metabolic surface markers further revealed increased expression of GLUT1 on CD4+ T cells in IDHwt patients, indicating an activated CD4+ repertoire compared to HD. CONCLUSION: Taken together, our results show a CD4+ TH cell type specific skewing of the peripheral immune repertoire in patients with IDHwt gliomas. Our data highlights the importance of considering malignant glioma as a disease with profound systemic effects fundamentally altering the immune repertoire in affected patients.